Evaluation of different methods to improve culture-negative peritoneal dialysis-related peritonitis: A single-center study - Duangrat Tanratananon (2022)
Background: ISPD recommends culture-negative peritonitis in each peritoneal dialysis (PD) center should less than 15%. The hospital in Thailand, however faced a significantly high rate of culture negative peritonitis, even using blood culture bottles technique. This study evaluates the performance of three different culture methods in detecting organisms in PD related peritonitis. Methods: A prospective cohort diagnostic study was performed in PD patients diagnosed with PD related peritonitis in Surin Hospital from October 2018 to June 2020. The Diagnosis of peritonitis was followed ISPD guidelines. PDF sample from each patient was processed by three different blood culture bottle-based techniques, including i) 50 ml PDF centrifugation, and ii) 10 ml PDF centrifugation before inoculated into blood culture bottles, and iii) inoculation into blood culture bottles without centrifugation. The sensitivities and isolated organisms were compared among the individual methods. Results: Of 126 PD patients with clinical peritonitis, PD related peritonitis was diagnosed in 87 patients with 105 PDF analysis. PDF culture showed gram-positive organisms 34%, gram-negative organisms 41%, fungal 5.71%, and culture-negative result in 22.86%. The direct blood culture method was positive in 59.05%, while centrifugation before inoculated into blood culture bottles, has a higher percentage of positive results, 60.95% and 64.76% from 10 ml to 50 ml PDF volume; respectively. The sensitivity was 84% and 76.5% for 50 ml PDF centrifugation and blood culture without centrifugation. Conclusion: Large volume PDF centrifugation before inoculating into blood culture bottles may improve the positive culture rate in PD related peritonitis.